Digital Victim: Castellian Perspective on Education in Rural Indonesia - Juwita, Rina; Purwanti, Silviana; Rohmah, Ainun Nimatu (UI Scholars Hub, 2021)
Covid-19 has presented a new set of challenges in every area; higher education is one of them. The pandemic has resulted in a shift in teaching and learning communication methods, creating a new structure for digital-based education. This study investigates this phenomenon through the perspective of Castells’ Network Society Theory to see the relational capacity of education in rural Indonesia. In his view, Castells summarized a distinctive concept between the flow of time and space in a networked society. The current space deals specifically with the center of social organization today where places around the world have been connected in a dynamic sector. As geographic discontinuity serves as a source of relational chaos, context and innovation will determine how a place prospers or decline, even though all will be integrated into the network society. Therefore, it is important to identify opportunities and challenges in the current scenario so that academic and government leaders can address them through the right innovations. This study conducted a survey to determine the perceived conditions of online learning by students. In addition, this study also used secondary data from scientific journals, government and non-government publications, books from various authors, websites, and public data as well as various other sources of information. The results of this study indicate that the provisions of online learning are new to limit the learning process in several ways, such as networks, costs, and interactions between lecturers and students. In the perspective of the Castells’ Network Society Theory, the resuts of this study see students and lecturers as digital victims, especially in the context of teaching and learning.